Redifferentiation of dedifferentiated chondrocytes in a novel three‐dimensional microcavitary hydrogel. Issue 5 (20th August 2014) - Zeng, Lei; Chen, Xiaofeng; Zhang, Qing; Yu, Feng; Li, Yuli; Yao, Yongchang
Abstract: Although chondrocytes exist in native cartilage all over the body, it is still a challenge to use them as therapeutic cells for cartilage tissue engineering (TE) because of their easy dedifferentiation in in vitro culture. An improved culture system to maintain the characteristics of chondrocytes or recover their chondrocytic phenotype should be developed. In this study, we have set up an innovative microcavitary alginate hydrogel in an easy way. We compared this culture system with the conventional hydrogel and found that the microcavitary hydrogel exhibited outstanding superiorities in helping the dedifferentiated chondrocytes recover the capability for synthesizing cartilaginous extracellular matrix. In addition, we explored the correlation between chondrocyte redifferentiation in microcavitary hydrogels and changes in p38 and Erk1/2 activity. Our findings indicated that this microcavitary hydrogel would be a promising culture system to provide sufficient competent cells for cartilage regeneration and TE. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1693–1702, 2015.